Pragmatics Analysis on Students’ Conversation at Grade Eleven of State of Vocational High School 1 Pematangsiantar - Cindya Septiany Simanjuntak; Herman Herman; Dumaris E Silalahi; Rolan Manurung; Arwin Tannuary; Desi Afrianti (CV. Creative Tugu Pena, 2023)
This research was intended to find out the kinds of maxim on students’ conversation at grade eleven of State of Vocational High School (SMK Negeri) 1 Pematangsiantar. This research used descriptive qualitative which the data were obtained through students' conversations about expressing opinions. The subject of this research was the students of SMK Negeri 1 Pematangsiantar at grade eleven in the academic year 2023/2024. The instrument of this research was mobile phone, because the classroom interaction flows quickly, mobile phone was needed to help capturing students’ conversation. The data were collected by using the voice recordings and the transcripts. The data were analyzed based on students' conversations, then classified based on the maxims used in the conversation into each type of maxim, the maxims are then calculated to find the dominant maxim. The result of this research showed that the students used maxim of quantity (18,8%), maxim of quality (21,9%), maxim of relation (6,3%) and maxim of manner (18,8%). It showed that the students’ conversation dominant used maxim of quality in their conversation to express opinions. Keywords: Pragmatic Analysis, Maxim on Coversation, Expressing Opinions